Circular RNA expression in cutaneous squamous cell carcinoma. Issue 3 (September 2016) - Sand, Michael; Bechara, Falk G.; Gambichler, Thilo; Sand, Daniel; Bromba, Michael; Hahn, Stephan A.; Stockfleth, Eggert; Hessam, Schapoor
Highlights: CircularRNAs (circRNAs) have pivotal impacts on the cellular regulatory network. CircRNAs sequester microRNAs (miRNAs) with miRNA response elements (MREs). A total of 322 circRNAs were identified as differentially expressed in cSCC. A total of 1603 MREs were identified as part of differentially expressed circRNAs. Complementary MRE sequence was identified in 23 miRNAs known to be cSCC relevant. Abstract: Background: CircularRNAs (circRNAs) are a reinvented class of abundant, stable, and evolutionary conserved non-coding RNAs with pivotal impacts on the cellular regulatory network and epigenetics by sequestering microRNAs (miRNAs) like a sponge. Objective: Purpose of the present study was to investigate circRNA expression in cutaneous squamous cell carcinoma (cSCC). Methods: A total of six cSCC and six non-lesional skin (control) biopsies were harvested. Microarray based circRNA expression was determined in the cSCC (n = 3) and compared with the non-lesional skin (n = 3) from a group of 13, 617 distinct human circRNAs found in the Arraystar circRNA Array V2.0 (Arraystar, Rockville, USA). Microarray data were validated by quantitative real-time reverse transcription polymerase chain reaction in a separate group (cSCC, n = 3 and non-lesional skin, n = 3). miRNA binding to miRNA response elements (MREs) sequence data were acquired bioinformatically. Further data mining was performed to identify circRNAs containing MRE sequences that interacted with previously described miRNAs playing a role in cSCC formation. Results: A total of 322 circRNAs (143 up- and 179 down-regulated; fold change ≥2 and p < 0.05) were identified as differentially expressed in cSCC. Furthermore, we identified a total of 1603 MREs that were part of the differentially expressed circRNAs. Among those circRNAs, a complementary MRE sequence was identified in 23 miRNAs previously known to be cSCC relevant. Conclusion: This study showed that circRNAs are differentially expressed in cSCC and play an important role in tumor formation by interfering with cSCC relevant miRNAs through miRNA sequence complementary MREs participating in epigenetic control.